2017
DOI: 10.1088/1757-899x/228/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Validation of X-ray radiography for characterization of gas bubbles in liquid metals

Abstract: Optimization of exposure factors for X-ray radiography non-destructive testing of pearl oyster Susilo, I Yulianti, A Addawiyah et al.-A Thermoluminescent Radiography Akira Doi, Takashi Kanie and Akira Naruse -Development of 4.5 keV monochromatic X-ray radiography using the high-energy, picosecond LFEX laser H Sawada, S Fujioka, T Hosoda et al. Abstract. X-ray radiography has proved to be an efficient and powerful tool for the visualization of two-phase flows in non-transparent fluids, in particular in liquid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…XR and XCT methods allow for direct observation of bubble shapes. However, x-ray based techniques are, in general, very constrained by relatively small liquid metal thickness in the beam direction due to intense x-ray attenuation by liquid metals [20][21][22][23][24]. XCT, while offering very high temporal resolution and sufficient phase boundary detection precision, also entails experimental systems that are rather susceptible to applied MF, rendering them hardly applicable to studies of magnetohydrodynamic (MHD) bubble flow [25][26][27].…”
mentioning
confidence: 99%
“…XR and XCT methods allow for direct observation of bubble shapes. However, x-ray based techniques are, in general, very constrained by relatively small liquid metal thickness in the beam direction due to intense x-ray attenuation by liquid metals [20][21][22][23][24]. XCT, while offering very high temporal resolution and sufficient phase boundary detection precision, also entails experimental systems that are rather susceptible to applied MF, rendering them hardly applicable to studies of magnetohydrodynamic (MHD) bubble flow [25][26][27].…”
mentioning
confidence: 99%
“…Images with a good intensity contrast and low signal-to-noise ratio can only be achieved by using a flat geometry of this kind. Previous measurements [18,21,22] have shown that a gap of D ¼ 12 mm is a good compromise. On one hand, the image contrast obtained in this configuration is sufficient to clearly visualize bubbles and gas-liquid interfaces; on the other hand, the moderate geometric restriction still allows for the development of sufficient dynamics of both the bubble plume and the free surface of the melt.…”
Section: The Experimental Setupmentioning
confidence: 97%
“…The applicability of X-ray radiography for quantitative measurement of bubbles rising in a stagnant liquid was already validated in previous studies. [21] In all the experiments presented here, the size of the observation window was approximately 106 Â 156 mm 2 (1730 Â 2560 px 2 ), yielding a spatial resolution of each pixel of l px ¼ 0:061 mm: The difference between the very high attenuation of X-ray radiation of the liquid metal and the extremely weak attenuation of Ar leads to a clear contrast in the resulting images. The local image intensity correlates with the fraction of gas at a specific position in the yÀz plane.…”
Section: The Experimental Setupmentioning
confidence: 98%
See 2 more Smart Citations